Maternal and perinatal outcome in placenta previa - one year study in tertiary care center in Tamil Nadu, India - R., Raja Rajeshwari; M., Rubini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Obstetric hemorrhage is one of the most dangerous and devasting group of disorders in Obstetrics of which placenta previa contributes 1/5th of the cases. The aim of this study was to analyze the obstetrical factors and the maternal and perinatal outcome of these cases. Methods: This was a retrospective study conducted in the Department of Obstetrics and Gynecology of Thanjavur Medical College Hospital, Thanjavur from August 2014 - July 2015. Chart records of all women who had undergone cesarean section for placenta previa were reviewed. Relevant clinical findings were noted. Results: In the present study, 134 cases of placenta previa were studied regarding type of clinical presentation, clinical course, maternal and perinatal outcome. Information obtained was arranged statistically. A placenta previa case was highest in the age group 20-29 years (79.85%) and in multiparous group (63.43%). Most common risk factor was previous cesarean section (39.5%) followed by abortion in 24.6%. Major degree of placenta previa constitutes 69.4% i.e., majority of cases and minor degree constitutes 30.59% of cases. In the present study massive blood transfusion was required in 0.04% of all cases, adherent placenta previa in 1.9%, 12.68% required hysterectomy. Perinatal morbidity was 25.92% and perinatal mortality incidence was 16.41%. Prematurity contributed the most 63.6% followed by RDS about 4.58%. Newborn with weight above 2 kg has very good survival rates, whereas newborn with weight <1 kg has poor survival rates. Conclusions: Placenta previa poses danger to both the mother and the baby with high maternal morbidity and adverse perinatal outcome.